2010
DOI: 10.1109/ms.2009.154
|View full text |Cite
|
Sign up to set email alerts
|

The rise and fall of the Chaos report figures

Abstract: I E E E S o f t w a r E P u b l i s h e d b y t h e I E E E C o m p u t e r S o c i e t y0 7 4 0 -7 4 5 9 / 1 0 / $ 2 6 . 0 0 © 2 0 1 0 I E E E focus management hardly help increase project success. Over the years, their figures have attracted tremendous attention.However, we question the validity of their figures. Robert Glass 2,3 and Magne Jørgensen and his colleagues 4 indicated that the only way to assess the Chaos results' credibility is to use Standish's data and reiterate their analyses. But there's ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(96 citation statements)
references
References 8 publications
2
90
0
4
Order By: Relevance
“…It is noted that up to 70% of SDPs result in failure [16], [17]. The study conducted by Elmam and Koru [3] indicates that the top 5 causes of project failure are non-technical issues.…”
Section: B Causes Of Software Project Failurementioning
confidence: 99%
“…It is noted that up to 70% of SDPs result in failure [16], [17]. The study conducted by Elmam and Koru [3] indicates that the top 5 causes of project failure are non-technical issues.…”
Section: B Causes Of Software Project Failurementioning
confidence: 99%
“…This is in contrast to the 2004 study conducted by The Standish Group, which reported a higher success rate for IT projects at 29 per cent [18]. The Standish Chaos Report for 2006 showed that 35 per cent of IT projects were successful, which decreased by 3 per cent to a 32 per cent success rate, according to their 2009 study [18].…”
Section: Introductionmentioning
confidence: 72%
“…For example in a study conducted by PriceWaterhouseCoopers in 2004, 10 640 IT projects were surveyed and revealed that only 2.5 per cent of organisations achieve budget, scope and schedule targets in all IT projects [13]. This is in contrast to the 2004 study conducted by The Standish Group, which reported a higher success rate for IT projects at 29 per cent [18]. The Standish Chaos Report for 2006 showed that 35 per cent of IT projects were successful, which decreased by 3 per cent to a 32 per cent success rate, according to their 2009 study [18].…”
Section: Introductionmentioning
confidence: 96%
“…El estudio del éxito de los proyectos de software ha sido un tema de gran atención desde hace más de una década, en la que se ha tratado de analizar los factores que colaboran al cumplimiento completo de un desarrollo y la manera como las empresas tratan de evitar posibles fracasos. Un ejemplo fue el análisis realizado [1] sobre las estadísticas del Standish Group de proyectos exitosos donde evidenciaba que el crecimiento de efectividad de los proyectos entre 2000 y 2004 había sido solo de un 1%, situación que mejora al 2009 con un 4%. Cabe aclarar que con el paso de los años los factores tenidos en cuenta para el estudio han estado ampliándose para hallar con más efectividad una respuesta [2].…”
Section: Introductionunclassified